Scholarship of Teaching and Learning (SoTL) : Training of Trainers - Rohana Othman, author.; Ngeow, Yeok Meng, author. 530860; Narina A. Samah, author. 525682; Aishah Abu Bakar, author.; Raja Maznah Raja Hussain Project Leader 323976 (Kuala Lumpur University of Malaya Press, 2018)
Volume 1 : Basic level -- volume 2 : Intermediate level -- volume 3 : Advanced level -- volume 4 : Report.